THE USE OF NUMBERED HEADS TOGETHER TO TEACH DESCRIPTIVE TEXT TO THE SEVENTH GRADERS OF SMP NEGERI 1 KOTA MOJOKERTO (RETAIN, 2014)
Abstrak Membacaadalahsalahsatudariempatketerampilanpenting yang harusdikuasaiolehsiswa di semuakelas, daripadamendengarkan, berbicara, danmenulis.Denganmembaca, parasiswaakanmendapatkanlebihbanyakpengetahuandaninformasi. Keterampilaninisamapentingnyadenganketerampilanlainnya. Kenyataannya, beberapa guru hanyamengajarmembacacaramonoton. Hal inimembuat guru harusmenemukancara yang menarikuntukmengajarkannya. Berdasarkanpermasalahantersebut, guru dapatmenggunakanteknik Numbered Heads Together sebagaiteknikalternatifdalampengajaranmembaca.Penelitimelakukanpenelitian di SMP Negeri 1 Kota Mojokerto. Berdasarkan fakta di atas, peneliti melakukan penelitian pada Numbered Heads Together teknik untuk mengajarkan teks deskriptif untuk kelas tujuh SMP. Penelitian ini bertujuan untuk mendeskripsikan pelaksanaan Numbered Heads Together dalam mengajar teks deskriptif untuk siswa kelas tujuh dan untuk menggambarkan pemahaman bacaan siswa saat pelaksanaan Numbered Heads Together dalam mengajar teks deskriptif untuk siswa kelas tujuh. Rancangan penelitian ini adalah penelitian deskriptif kualitatif. Subyek penelitian ini adalah siswa kelas tujuh SMP Negeri 1 Kota Mojokerto. Data penelitian ini dikumpulkan dari hasil lembar observasi dan hasil tugas siswa. Hasil penelitian ini menunjukkan bahwa pelaksanaan Heads Together Numbered mendorong siswa untuk berpartisipasi aktif dalam seluruh kegiatan. Setelah menggunakan teknik ini, siswa saling membantu untuk memahami teks serta menjawab pertanyaan-pertanyaan dari teks. Selain itu, jumlah siswa yang mendapatkan prestasi yang baik meningkat dari satupertemuan ke pertemuan lain. Artinya pemahaman membaca siswa lebih baik setelah pelaksanaan Numbered Heads Together. Kesimpulannya, Numbered Heads Together adalah teknik yang bagus untuk digunakan dalam mengajar teks deskriptif, terutama untuk siswa kelas tujuh, karena membantu siswa untuk mengatasi kesulitan mereka dalam membaca, menciptakan suasana yang positif di kelas, dan bangunan interaksi yang baik bagi guru dan siswa. Kata Kunci: Numbered Heads Together,teksdeskriptif, membaca Abstract Reading is one of the four important skills that have to be mastered by students in all grades, instead of listening, speaking, and writing. By reading, students will get more knowledge and information. This skill is as important as other skills. In reality, some teachers only teach reading monotonous way. It makes the teacher must find an interesting way to teach it. Based on that problem, the teacher can use Numbered Heads Together technique as the alternative technique in teaching reading. The researcher conducts a research in SMP Negeri 1 Kota Mojokerto. Based on the fact above, the researcher conducted a study of Numbered Heads Together technique to teach descriptive text to the seventh grade of junior high school. This study aimed to describe the implementation of Numbered Heads Together in teaching descriptive text to the seventh graders and to describe the students’ reading comprehension when the implementation of Numbered Heads Together in teaching descriptive text to the seventh graders. The design of this study is descriptive qualitative research. The subjects of this study are the seventh graders of SMP Negeri 1 Kota Mojokerto. The data of this study are collected from the result of observation checklist and the result of students’ task. The result of this study shows that the implementation of Numbered Heads Together encourages the students to participate actively in the whole activities. After using this technique, the students help each other to comprehend the text as well as answer the questions of the text. In addition, the number of students who get good achievement increasing from one meets to another. It means that the students’ reading comprehension is better after the implementation of Numbered Heads Together. In conclusion, Numbered Heads Together is a good technique to be used in teaching descriptive text, especially for the seventh graders, since it helps the students to overcome their difficulties in reading, creates a positive atmosphere in the class, and buildings a good interaction for teacher and students. Keywords:numbered heads together, descriptive text, reading